2019
DOI: 10.1002/mc.23038
|View full text |Cite
|
Sign up to set email alerts
|

Aminocyanopyridines as anti‐lung cancer agents by inhibiting the STAT3 pathway

Abstract: Lung cancer is a leading cause of cancer-related death worldwide. Cyanopyridines and aminocyanopyridines with carbon-nitrogen bonds have been proved to exert significant anticancer, antibacterial, and anti-inflammatory effects. In this study, we showed that aminocyanopyridine 3o and 3k displaying potent antitumor activity via inhibiting the signal transducer and activator of transcription 3 (STAT3) pathway. They blocked the constitutive STAT3 phosphorylation in a dose-and time-dependent manner and regulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…To maintain conformational stability, compound 32 also forms two hydrogen bonds with residues Ser-63 and Glu-638. [27] STAT3 is considered to be a major oncogene in the development of colorectal cancer. [28] Therefore, inhibiting STAT3 seems to be a promising cancer treatment.…”
Section: Survivin Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain conformational stability, compound 32 also forms two hydrogen bonds with residues Ser-63 and Glu-638. [27] STAT3 is considered to be a major oncogene in the development of colorectal cancer. [28] Therefore, inhibiting STAT3 seems to be a promising cancer treatment.…”
Section: Survivin Inhibitorsmentioning
confidence: 99%
“…To maintain conformational stability, compound 32 also forms two hydrogen bonds with residues Ser‐63 and Glu‐638. [ 27 ]…”
Section: Biological Activities Of Cyanopyridinesmentioning
confidence: 99%
“…Aminocyanopyridines can inhibit cell proliferation and induce cell death in human cancer cells by inhibiting the STAT3 pathway 17. We next validated the effects of 3n on STAT3 signaling in three colorectal cancer cells.…”
Section: Resultsmentioning
confidence: 95%
“…There are relatively few reports on 3-amino-3-cyanopyridine compounds compared to 2-amino-3-cyanopyridine compounds, and there are few studies on the anti-tumor activity of such compounds 16. Our group has previously demonstrated that the aminocyanopyridines exhibit significant antitumor activity against lung cancers in vitro and in vivo 17. So we continued our previous studies to further design, synthesize and evaluate the in vitro anticancer activity of a series of aminocyanopyridines.…”
Section: Introductionmentioning
confidence: 96%
“…43 There are not many systems available that are more viable in terms of environmental protection and atom economy. Among the nitrogen heterocyclic compounds, aminocyanohydropyridine derivatives are important motifs for organic synthesis and are widely found in many natural products, having different biological activities such as antimicrobial agents, 44 anticancer agents, 45 psychotropic, 46 anti-allergenic, 46 anti-inflammatory, 46 and estrogenic activities, and MK-2 kinase inhibitors 7 (Fig. 1 compound I , II ).…”
Section: Introductionmentioning
confidence: 99%